2001
DOI: 10.1007/s001980170148
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density of 704 Amateur Sportsmen Involved in Different Physical Activities

Abstract: The aim of the study was to analyze the relation between sports and bone mass. Seven hundred and four men with no history of chronic disease were questioned on their adolescent and adult sporting activities. Their total body (TB) and regional (head, spine, arms and legs) bone mineral density (BMD) were measured by dual-energy X-ray absorptiometry. BMD measurements and ratios of regional BMD to TB BMD were compared using a multiple regression analysis. Probands (mean age 30 years) were engaged in 14 sports acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 27 publications
3
92
2
7
Order By: Relevance
“…72 In highly active SCI patients, Jones et al 31 reported that upper limb bone mass is preserved while a significant demineralization can be noted in the lower body. The beneficial effect at the upper limbs was observed whatever the level of lesion and even in tetraplegic individuals who have been reported to be at risk for demineralization at these sites.…”
Section: Physical Exercisementioning
confidence: 99%
“…72 In highly active SCI patients, Jones et al 31 reported that upper limb bone mass is preserved while a significant demineralization can be noted in the lower body. The beneficial effect at the upper limbs was observed whatever the level of lesion and even in tetraplegic individuals who have been reported to be at risk for demineralization at these sites.…”
Section: Physical Exercisementioning
confidence: 99%
“…5,13,14 In the able-bodied population, exercise has been shown to have an osteogenic in¯uence, with the greatest bone mass preservation or increase at sites which are loaded intermittently. 15 ± 18 Morel et al 15 found arm BMD to be greatest in sportsmen involved in rugby, ®ghting sports, basketball, volleyball, handball and bodybuilding, and the increased bone mass in the dominant arm of tennis players is well documented. 19 Similarly exercise has been used to reduce the extent of skeletal dimineralisation in both space¯ight, 20 and in the spinal cord injured population.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of high level sport training on bone may differ according to the specific constraints of the various activities practiced, to the amplitude and repetition of the constraints they induce, and to the bone sites on which load is applied. Cross-sectional studies in athletes report a positive effect of intense physical exercise on BMD (1). A traditional example is that of tennis players whose BMD is significantly increased on the dominant arm (18).…”
Section: Discussionmentioning
confidence: 99%